Chemical bonding and dynamic fluxionality of a B15+cluster: a nanoscale double-axle tank tread - Wang, Ying-Jin; You, Xue-Rui; Chen, Qiang; Feng, Lin-Yan; Wang, Kang; Ou, Ting; Zhao, Xiao-Yun; Zhai, Hua-Jin; Li, Si-Dian (Physical Chemistry Chemical Physics, 2016)
A planar, elongated B15(+) cationic cluster is shown to be structurally fluxional and functions as a nanoscale tank tread on the basis of electronic structure calculations, bonding analyses, and molecular dynamics simulations. The outer B11 peripheral ring behaves like a flexible chain gliding around an inner B4 rhombus core, almost freely at the temperature of 500 K. The rotational energy barrier is only 1.37 kcal mol(-1) (0.06 eV) at the PBE0/6-311+G* level, further refined to 1.66 kcal mol(-1) (0.07 eV) at the single-point CCSD(T)/6-311G*//CCSD/6-311G* level. Two soft vibrational modes of 166.3 and 258.3 cm(-1) are associated with the rotation, serving as double engines for the system. Bonding analysis suggests that the "island" electron clouds, both σ and π, between the peripheral ring and inner core flow and shift continuously during the intramolecular rotation, facilitating the dynamic fluxionality of the system with a small rotational barrier. The B15(+) cluster, roughly 0.6 nm in dimension, is the first double-axle nanoscale tank tread equipped with two engines, which expands the concepts of molecular wheels, Wankel motors, and molecular tanks.